El internet, las redes sociales, los nuevos medios y su incidencia en el desempeño laboral de las secretarias del Centro de Admisión y Nivelación Universitaria de la Universidad Técnica de Babahoyo - Vargas Guevara, Génesis Solange (2020)
For the investigation of this case study, the research line of Management and Public Administration was applied with the sub-line of Activities of Executive Level of the Secretaries in the Public Company, which is related to the topic of the Internet, Social Networks and the new media and its impact on the Secretaries of the Admission and Leveling Center of the Technical University of Babahoyo. This research was carried out at the CANU of the UTB which is located in the Babahoyo canton, the secretaries are the fundamental pillar of a company, these administrative assistants are the ones who perform the tasks in a certain office or administrative department, apart from handling business confidential character, therefore and according to their functions and tasks they become practically the right hand of the boss. The internet is essential in our daily lives and in the workplace of the secretariats, mastering these new media must be essential because within their functions their professional performance must be effective. The Secretary of the University Admission and Leveling Center has within its functions is to attend to students who have obtained a place in the Technical University of Babahoyo through Higher Education, Senescyt, in this study the impact it has on the secretaries the internet, social networks and new media in their work performance and it is deduced that there is a good service to the user, which in this case are the students applying to enter the Pre-University. Technology is continually changing and these administrative assistants are updated as time goes by, since this enrollment process is purely digital and has a good impact on the secretariats of this center, which is the University Admission and Leveling Center, some of These students do not handle the new digital media, but here are the CANU secretaries to facilitate the enrollment process. In this case study, the techniques of both surveys and interviews were applied by question that by means of the questionnaire of questions executed to the administrative assistants of the University Admission and Leveling Center, it was possible to obtain much more specific information than was expected. These secretaries have a good command of these new digital media